Mortgage in Bulgaria and Romania - Does the "Foreignness" Influence The Supply? (UNWE Yearbook, 2021)
The housing markets and housing finance are tightly connected and both are crucial to the stability of the economy as a whole. Housing booms and busts have been associated with many of the most serious financial and economic crises in developed countries. In order to avoid such crises in the future IMF research suggests it is particularly important to monitor credit growth.  The connection between housing markets and housing finance can be seen in the mortgage interest rates. Even though the main drivers of mortgage interest rates are well known in the theory, differences between countries still exist. Nowadays banking has become international, mortgage-lending markets are predominantly local. In fact, even pan-European banks operate on non-integrated national mortgage credit markets. In our study we explore the ability of main mortgage loan clauses to provide a robust clusterization of market participants.